Network Attention and Earnings Drift - Chunying, Chen; Chiunghua, Hsieh (International Journal of Economics and Financial Issues, 2019)
For the first time, this article uses the search volume index (SVI) of Google Trends to measure investor attention and observe stock market. Empirical results show that the higher the attention to individual stocks, the lower the cumulative abnormal returns. If stocks had positive (negative) abnormal returns, the cumulative abnormal returns would decline, thereby weakening (strengthening) earnings drift. Only the stocks with earnings that weren’t as good as expected encountered an increase in cumulative abnormal returns. Regarding stocks that attract investor attention, having a positive (negative) earnings surprise brings more positive (negative) cumulative abnormal returns and strengthens (weakens) earnings drift. Keywords: Earnings drift; search volume index; investor attention JEL Classifications: G1, J3 DOI: https://doi.org/10.32479/ijefi.7975